2011
DOI: 10.1148/radiol.11102277
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson Disease: Diagnostic Utility of Diffusion Kurtosis Imaging

Abstract: Diffusion kurtosis imaging in the basal ganglia, as compared with conventional diffusion-tensor imaging, can improve the diagnosis of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(214 citation statements)
references
References 38 publications
17
182
6
1
Order By: Relevance
“…Although our method could not discriminate 2 groups perfectly (i.e., there were overlaps in SNc volumes), it could discriminate PD patients from control subjects with almost equal or better performance compared with other imaging methods, such as contrast ratio method using neuromelanin images [7,8], and diffusion-kurtosis imaging [16]. Therefore, our method can be potentially used for clinical diagnosis of PD patients, especially for early stage.…”
Section: Discussionmentioning
confidence: 87%
“…Although our method could not discriminate 2 groups perfectly (i.e., there were overlaps in SNc volumes), it could discriminate PD patients from control subjects with almost equal or better performance compared with other imaging methods, such as contrast ratio method using neuromelanin images [7,8], and diffusion-kurtosis imaging [16]. Therefore, our method can be potentially used for clinical diagnosis of PD patients, especially for early stage.…”
Section: Discussionmentioning
confidence: 87%
“…76 FA of the cingulate 77 and Wang's team showed that the mean kurtosis of the ipsilateral substantia nigra performed best in diagnosing Parkinson disease (sensitivity, 0.92; speciˆcity, 0.87), compared with conventional diŠusion metrics including FA, mean diŠusivity, axial diŠusivity, and radial diŠusivity. 78 Therefore, non-Gaussian DWI and DKI, in particular, may be promising for the evaluation of degenerative changes in vivo.…”
Section: Neuropsychiatric Diseasementioning
confidence: 99%
“…To our surprise, computation time differed only slightly among the derived methods for 6 b-values-GCF, WGCF, SOR, MOR, NS, and BNS. This can be due to pre-computation of several constant values, $ i0 , of [10], which are independent of signal values. Such methods as SOR, MOR, and BNS with several choices for minimizing residuals took slightly more time than the baseline methods of GCF and JCF, but the increase was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike DTI and its matured metrics, such as fractional anisotropy (FA), DKI and its derived parameters are in development. However, several reports of clinical applications reveal important features of DKI, such as its potential usefulness in diagnostic imaging to evaluate neurological issues in aging 4 and disorders including stroke, 5 Alzheimer's disease, 6 schizophrenia, 7 glioma, 8,9 Parkinson disease, 10 and attention deficit hyperactivity disorder. 11 Recent trials on DKI in such regions as the liver 12 and spine 13 have also been reported.…”
Section: Introductionmentioning
confidence: 99%